Extract of cell culture Rejasa (Elaeocarpus grandiflorus) Decrease Blood Glucose Through Insulin Receptor Pathway (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
Diabetes mellitus is a metabolic disease characterized by the high blood glucose levels. The high prevalence of Diabetes Mellitus needed an innovation in prevention, treatment and control of case. Rejasa (Elaeocarpus grandiflorus) is one of plants has the potential to develop as an antidiabetic. The pretest and posttest control group design were conducted to 30 Rattus norvegicus Wistar strain. The rats induced alloxan monohydrate intraperitoneally at dose of 125 mg/kg BW once day until the blood glucose above 200 mg/dL The hyperglycemic rats were divided into 5 groups, that were negative control (K-), positive control (K+, given glibenclamide 0.072 mg/200 gBW), P1 (given E. glandiflorus cell extract 1 mg/kgBW), P2 (given E. glandiflorus cell extract 10 mg/kgBW), and P3 (given E. glandiflorus cell extract 100 mg/kgBW). The rats were given E. glandiflorus and glibenclamide orally for 10 days. Measurement of blood glucose levels was carried out on day 0 and day 10, after 10 h fasting. The mechanism of antidiabetic effect of E. glandiflorus was explored by in silico. The mean of blood glucose levels on day 0 were 455.2 mg/dL (K), 422.8 mg/dL (K+), 469.8 mg/dL (P1), 355.5 mg/dL (P2) and 446 mg/dL (P3). The blood glucose levels on day 10 were 367.8 mg/dL (K-), 89.6 mg/dL (K+), 285.6 mg/dL (P1), 136.8 mg/dL (P2) and 104.8 (P3). Statistical analysis showed the difference between K- from P2(p=0.015) and P3 (p0.001). When compared with K+, only P3 showed no difference (p=0.873). Flavonoid of E. glandiflorus act on insulin receptor pathway and involved HK2, PTPN1, AKT1, PI3KR1, HRAS and GSK3B protein. These results showed that extract cell of E. glandiflorus have antidiabetic activity on insulin receptor pathway.